Pengetahuan Konsumen Tentang LPG Bersubsidi di Indonesia - Joni Fernandes (JURNAL PUNDI, 2018)
The aim of this study is to analyze the main factors of consumer knowledge about the official retail price of subsidized LPG and consumer knowledge that the 3 kg LPG is subsidized by the government of Indonesia. This study uses survey logistic regression (SVY logit) as a method of analysis. The results found that Communities in the city tend to be more aware that 3 Kg LPG is subsidized by the government than 2% in rural areas. There is no difference in the increasing education of respondents who live in rural than urban residents who live in the knowledge that the 3 kg LPG is subsidized by the government. Ignorance of the public on fossil fuels are subsidized by the government should not be ignored. The public ignorance will lead to resistance and demonstrations to reject any policy of elimination of fossil fuel subsidies, which in turn increase the price of subsidized fuel